Architecture and Culture in the Time of Shohrukh - o‘g‘li, Bozorov Quvonchbek Dilmurod; qizi, Uralova Aziza Dilmurod; Tojiddinovich, Yuldashov Ulug’bek (International Journal on Integrated Education, 2022)
During the reign of Shah Rukh, there was a library with rare works of his time. The library was famous all over the world. In particular, the Sultan of Egypt, Sultan Chakmak, sent special envoys to Khorasan and published five rare works in Shah Rukh's library: asks him to give his works as a gift. Shah Rukh, a rare genius, ordered that a copy of these works be sent to him, not to the library. This would have added even more fuel to Burns' already significant marketing momentum.